2008
DOI: 10.1590/s0103-507x2008000300002
|View full text |Cite
|
Sign up to set email alerts
|

Análise comparativa da complacência do sistema respiratório em três diferentes posições no leito (lateral, sentada e dorsal) em pacientes submetidos à ventilação mecânica invasiva prolongada

Abstract: Análise comparativa da complacência do sistema respiratório em três diferentes posições no leito (lateral, sentada e dorsal) em pacientes submetidos à ventilação mecânica invasiva prolongada

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
4
1
3
Order By: Relevance
“…Although the literature reports improved respiratory system compliance in the sitting position compared to the dorsal and lateral decubitus positions, ( 8 ) our study revealed a reduction of these values at greater angles, possibly due to the higher transthoracic pressure. However, it is not possible to state that this finding results from an increase in intra-abdominal pressure, as this variable was not evaluated; however, in all of our measurements, the legs were parallel to the ground to prevent further tilting with higher head positions.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Although the literature reports improved respiratory system compliance in the sitting position compared to the dorsal and lateral decubitus positions, ( 8 ) our study revealed a reduction of these values at greater angles, possibly due to the higher transthoracic pressure. However, it is not possible to state that this finding results from an increase in intra-abdominal pressure, as this variable was not evaluated; however, in all of our measurements, the legs were parallel to the ground to prevent further tilting with higher head positions.…”
Section: Discussioncontrasting
confidence: 80%
“…This condition was maintained for two minutes and followed by reduction of 2cmH 2 O per minute until the initial PEEP level was achieved. ( 8 ) After 30 minutes, the patients were placed in a controlled volume ventilation mode for evaluation of respiratory mechanics with the following parameters: tidal volume of 6 - 8mL/kg in relation to the ideal weight, 40 L/min flow, square wave flow, a respiratory rate of 15 breaths per minute, and an inspiratory pause time of 0.5 seconds. ( 9 ) These parameters were maintained for approximately two minutes in each position, and the peak and plateau pressure values and the mean PEEP were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…This finding was ascribed to a smaller dependent zone in this position, assuming that free zones are more compliant and thus favoring respiratory mechanics. (15) Another study reported on thoracic and abdominal expansibility, both in supine and active orthostatic positions, in healthy subjects. Thoracic expansion was greater during orthostatism, and abdominal expansion was greater in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…Nossos pacientes apresentavam a via aérea mais acessível, uma vez que eram traqueostomizados, mas, por outro lado, apresentavam caixa torácica rígida devido à imobilidade e restrição características de pacientes crônicos em leito de UTI. Isso possivelmente influenciou a mobilidade da secreção para remoção, pois é conhecido que o posicionamento corpóreo influencia diretamente os volumes e fluxos pulmonares -importantes para a remoção da secreção 17 .…”
Section: Variáveisunclassified